Pengaruh Umur Pindah Bibit dan Konsentrasi Pupuk Organik Cair NASA terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Erida Nurahmi; Fuadi Harun; Ikhwaluddin Ikhwaluddin (Fakultas Pertanian, Universitas Syiah Kuala, 2011)
Effect of Age Transplanting Seedling and NASA Liquid Organic Fertilizer Concentration on Cacao Seedling Growth (Theobroma cacao L.)ABSTRACT. The objective of this experiment was to study effect of age transplanting seedling and NASA liquid organic fertilizer concentration on cacao seedlings growth and to know interaction of the two factors. The experiment used randomized block design with factorial pattern. There were 2 factors that studied. First factor was age transplanting seedlings: age transplanting seedling 14, 21, and 28 days after seedling. Second factor was NASA liquid organic fertilizer concentration: 0.5; 1; 1.5; 2; and 2.5 ml/l water. The result showed that the best of cacao seedling growth on age transplanting seedling 21 days after seedling and NASA liquid organic fertilizer concentration 2,0 ml/l water. There was not significantly interaction between age transplanting seedlings with NASA liquid organic fertilizer concentration on all cacao seedling growth variables that studied.